Constructive classroom management : strategies for creating positive learning environments - Epanchin, Betty Cooper; Townsend, Brenda; Stoddard, Kim. (Pacific Grove, Calif. : Brooks/Cole Pub. Co, 1994)
"This practical guide for teachers centers on ways to help students manage their own behavior, rather than on ways their behavior can be managed by teachers, peers, parents, or other adults. Interventions focus on creating success, not on finding cures for problems. Attention is also given to behavior-management approaches within the context of school reform." "This proactive book features case material that illustrates the assessment, planning, implementation, evaluation, and reassessment process you will use in managing classroom behavior; an emphasis on considering situations from multiple points of view (the teacher and his or her feelings, the child, the parents, the other students in the classroom); vivid examples that demonstrate a wide variety of situations in special education and regular classrooms at both the elementary and the secondary level; and strategies for decreasing teacher "burnout.""
Include bibliographical references and index.
Keywords: Classroom management